Kelemahan Inspektorat Daerah dan Ketidakpatuhan Ketentuan Perundang-undangan Pada Praktek Audit Pemerintah Daerah di Indonesia - Susanto, Heri (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
This study developed astatistical model of non-complian cereporting provisions of law and control of the Inspectorate findings BPK audit opinion. The purpose of this study  was to analyze the  factors that affect  the out come of the Supreme  Audit  Agency audit opinion received by the local government. This study has selected 371 samples to the local government for the year 2014. Research using financial statement data in the formof  government  in  2014  soft  copy  of  the  Supreme  Audit  Agency  and  other publications. The  results  showed that non  compliance  reporting provisions  of  low  and Inspektorat control  weakness, has significant  effect  on  the administration  of the  BPK audit opinion.